Chemical-genetics identifies two mechanistically unique spiro-analogs: an inhibitor of bacterial iron homeostasis and a zinc chelator that re-sensitizes a metallo-beta-lactamase-producing pathogen to carbapenem antibiotics - Falconer, Shannon Beth (My University, 2014)
Concomitant with antibiotic use is the development of bacterial strains that are resistant to such compounds. Presently, the rate at which antibiotic-resistant pathogenic bacteria are emerging is outpacing our resupply of new antibacterials; therefore, renewed efforts to identify novel therapies are urgently needed. Transition metals are required by all life forms and, for bacteria, an adequate supply of nutrient metal is necessary to establish infection in a host. Indeed, as an antibacterial defense mechanism, eukaryotes have developed various means by which to restrict the availability of metal to the invading pathogen, thereby limiting its chances for successful colonization. As such, bacterial metal acquisition and homeostasis have been suggested as potential antibiotic targets to explore for the identification of new antibacterial small molecules. In this thesis I discuss my development of a high-throughput screening assay that specifically selects for compounds that perturb bacterial iron homeostasis. The results of this work led to the identification of a series of spiro-indoline-thiadiazole compounds that are toxic to bacteria via iron chelation. In addition to molecules that perturb the availability of bacterial intracellular iron, we present a series of spiro-indoline-thiadiazole analogs that inhibit bacterial growth by limiting zinc availability. Furthermore, we show that the respective zinc-perturbing analogs re-sensitize an otherwise drug-resistant strain of NDM-1-harbouring Klebsiella pneumoniae to carbapenem antibiotics. We discuss the potential for this class of compounds to serve as carbapenem adjuvants for treating infections caused by metallo-β-lactamase-containing pathogens.
Antibacterial activity through metal chelation
Keywords: Antibiotics, chemical genetics, high-throughput screening